Segmental testicular infarction: a case report - Tine Smets; Gina Reichman; Dirk P. J. Michielsen (Journal of Medical Case Reports, 2017)
Abstract Background Segmental testicular infarction is a very rare condition, which can mimic a testicular torsion or testicular cancer. Correct diagnosis is difficult but it is important to avoid unnecessary radical treatment. Case presentation We report a clinical case of a 36-year-old white man who presented at our emergency department with subacute testicular pain. A urine analysis, Doppler ultrasound, surgical exploration, blood analysis, and magnetic resonance imaging were performed to diagnose his condition, to exclude a testicular torsion, and to raise confidence in its non-malignancy. He was treated conservatively. At follow-up, a few months after the incident, he no longer had complaints. Ultrasonography showed remaining hypo-echogenicity of the left upper pole, indicating a sequel of ischemia. Conclusions Segmental testicular infarction is a rare condition which can be easily confused with a testicular torsion or a testicular tumor. This case report can be helpful in recognizing and diagnosing this condition. Making the right diagnosis is important since it can prevent an unnecessary radical treatment.